DESIGN AND PRODUCTION OF A DEVICE FOR BASING AND FIXING CONIC DETAILS IN SINE BAR MEASUREMENTS (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
The geometric features of the conical parts measured by a sine bar requires special devices for basing and fastening. Basing and fixing conical parts on a sine bar is a problem that can lead to deviations in measurements. In the presented study, a fixture for fixing and basing conical details when measuring with a sine bar is designed and manufactured. The device is designed to facilitate the work of the operator in fixing the workpiece during the measurement, which increases the accuracy of the measurements. The developed structure is designed using SolidWorks. After the completion of the 3D model, a choice of material and technology for 3D printing is made. After that, a 3D printer is used for its production. The manufactured device is tested in laboratory studies. The designed device is installed on the sine bar without changing the measurement methodology. The conducted experiments prove its workability and applicability.